Penyuluhan Penggunaan Angkak Sebagai Pewarna Alami Pada Pembuatan Saus Lokan Di Kelurahan Majelis Hidayah Kecamatan Kuala Jambi Kabupaten Tanjabtim - Monica, Metha; Setyaji, Hajar; Suryanto, Suryanto; Mukhsin, Mukhsin; Muis, Ridwan (Journal of Community Engagement Research for Sustainability, 2023)
Lokan is a type of shellfish and is one of the fishery products in the Majlis Hidayah Village, Kuala Jambi District, Tanjabtim Regency, Jambi Province. The village is an area on the east coast of Sumatra, approximately 70 km from the provincial capital of Jambi. Lokan meat has a chemical composition of 2.36 – 4.95% carbohydrates, 7.06 – 16.87% protein and 0.40 – 2.47% fat with an energy of 69 – 88 kcal/100 gram. (Hasan et al., 2014) in Pratiwi et.al. 2021. Lokan clams in the village of Majelis Hidayah are sold fresh and boiled and have never been made in processed form. The purpose of this community service activity is to provide counseling on the diversification of local processed products using natural colorant from Angkak. This community service activity involved 2 (two) groups of Fishermen's Families of Berkah and Anugrah located in the Majlis Hidayah Village, Kuala Jambi District, Tanjabtim Regency, Jambi Province. The implementation of this activity was carried out by counseling and demonstrating the making of lokan sauce to 2 (two) groups of fishermen's families. The output achieved was that the fishing family group Berkah and Anugrah were able to make local processed products into lokan sauce by using Angkak as a natural colorant, resulting in red lokan sauce. The conclusion of this community service activity is that the Berkah and Anugrah Fisherman Family Group can make local processed products into local sauce by using Angkak as a natural dye.